Abdominal esophageal removal - Esteves Edderman, Carlos; Andrade Zambrano, Trino (Revista Universidad de Guayaquil, 1986)
At the IESS Regional Hospital in the city of Guayaquil, the first case of Esophagectomy without Thoracotomy was performed, removing it through the Abdominal route, in a patient who had a total stenosis of the lower third of the Esophagus, after blunt dissection of the organ in the upper and third thirds. inferior, without complication of massive mediastinal bleeding. The Digestive Tract is reestablished with the Right Colon, taking it to the neck via Retrosternal route. Having the same results as described by Orringer and Akiyama, the advantages of this technique over those that perform Thoracotomy are analyzed.